Rumours in the coverage of armed conflicts: the Spanish media during the bombing of Yugoslavia in 1999 - Pérez Rastrilla, Laura (Historia y Comunicación Social, 2021)
The article presents the results of the analysis of rumours in the pieces of news published in El País, El Mundo, La Vanguardia and ABC, and broadcasted in Televisión Española and Telemadrid about the bombing of Yugoslavia, between February and June 1999. The detection and analysis of the rumours was carried out through a qualitative analysis. It was taken into account, firstly, the identification of the sources and, secondly, the process of verification of the published and broadcasted information. Journalists used different narrative formulas to disseminate information based in rumours, such as anonymous sources, collective and abstract agents, speculative expressions, conditional verbs and the appeal to authority.